Tricuspid annular plane systolic excursion is a predictor of mortality for septic shock. Issue 11 (24th October 2021) - Dong, Jun; White, Seth; Nielsen, Kirsten; Banchs, Jose; Wang, Jian; Botz, Gregory H.; Nates, Joseph L.
Abstract: Background: Cardiac dysfunction is a common sequela in patients with sepsis and multi‐organ dysfunction. Echocardiography is commonly used in the investigation of circulatory failure. Aims: We aimed to evaluate the prognostic value of echocardiographic parameters in patients with septic shock. Methods: This study was a retrospective trial. We included patients who were admitted to intensive care unit (ICU) with septic shock. The patients' echocardiograms, clinical data and outcomes were obtained from their medical records. Associations between echocardiogram variables and mortality were assessed using logistic regression, controlled for age, sex, body mass index and the interval between the ICU admission and echocardiogram. The utility of statistically significant echocardiogram variables to predict mortality were assessed using receiver operating characteristic (ROC) curves. Results: The outcomes presented that tricuspid annular plane systolic excursion (TAPSE) was statistically significantly associated with both ICU ( P = 0.02) and 90‐day ( P = 0.001) mortality. From the ROC curves, TAPSE emerged a significant and moderate predictor for 90‐day (area under curve (AUC) = 0.69, 95% CI = 0.565–0.814) and in‐ICU mortality (AUC = 0.762, 95% CI = 0.652–0.871). The optimal cut‐off for TAPSE was 2.1 cm for both 90‐day mortality (sensitivity of 80% and specificity and 58%) and in‐ICU mortality (sensitivity of 69% and specificity of 77%). Conclusions: TAPSE was associated with increased mortality in those with sepsis and suspicion of cardiac dysfunction. This is a hypothesis generating article that an association may be present and requires significant more work with expansion to the entire population base.